Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan: Survei Pada Karyawan Bagian Produksi PR. Makmur - Novita Dewi; Barin Barlian; Arga Sutrisna (BADAN PENERBIT STIEPARI PRESS, 2023)
This study aims to determine the effect of work discipline and work environment on Employee Performance (Survey on employees of the production of Public Relations.Prosperous). This study uses quantitative methods with a survey approach. The type of data used is primary data and secondary data, with a sample of 64 respondents from employees of the PR. Makmur prosper by using the method of convenience sampling techniques. Data analysis in this study using multiple regression analysis, correlation coefficient and coefficient of determination using SPSS software version 25. The results showed that work discipline and work environment simultaneously significantly affect employee performance. Work discipline partially insignificant effect on employee performance. The work environment partially has a significant effect on employee performance.